The Efficacy and Safety of Anlotinib in Pediatric Patients With Refractory or Recurrent Solid Tumors - Lu, Suying; Hong, Ye; Chen, Huimou; Wu, Liuhong; Sun, Feifei; Wang, Juan; Zhu, Jia; Que, Yi; Zhang, Lian; Zhen, Zijun; Sun, Xiaofei; Huang, Junting; et al. (Frontiers in Pharmacology, 2022)
Objective: Refractory or recurrent pediatric solid tumors lack effective treatments, and are associated with dismal outcomes. Hence, there is an urgent need for a novel therapeutic strategy. This study aimed to evaluate the efficacy and safety of anlotinib, a novel oral multi-kinase angiogenesis inhibitor, in pediatric patients with refractory or recurrent solid tumors. Methods: This single-institutional, observational retrospective study was conducted in Sun Yat-sen University Cancer Center, China. Refractory or recurrent pediatric solid tumor patients treated with anlotinib between 2018 and 2020 were evaluated. Results: Forty-one and 30 patients were enrolled to evaluate the efficacy and safety of anlotinib, respectively. There was partial response in 5 patients, stable disease in 22 patients, no patient with complete response, with an objective response ratio of 12.2% (5/41; 95% CI 1.7-22.7). The disease control rate was 65.9% (27/41; 95% CI 50.7-81) and the median progression-free survival was 2.87 months (95% CI 0.86-4.88). The incidence rates of any grade and grade 3-4 adverse events were 80% (24/30) and 23.3% (7/30), respectively. Bleeding (20%, 6/30), hand-foot syndrome (16.7%, 5/30), and diarrhea (13.3%, 4/30) were the most common adverse events. Grade 3-4 adverse events included hypertension, hand-foot syndrome, diarrhea, anemia, and thrombocytopenia. There were no adverse events-related deaths. Conclusion: For heavily pretreated pediatric solid tumors, anlotinib monotherapy and its combination with chemotherapy may be an effective treatment option with tolerable adverse events. It is necessary to monitor blood pressure when using anlotinib in children.